The Impact of Market Orientation and Pricing Strategy on Sustainable Business Performance: A Case Study of Tour & Travel Businesses - Christian Aprilio; Ali Wardhana (Universitas Pelita Harapan, 2025)
This study is motivated by the importance of market understanding in improving the competitiveness of tour & travel businesses, especially in the digital era where business actors must adapt to consumer needs. The purpose of this study is to analyze the effect of market orientation on business performance mediated by price strategy in tour & travel businesses in the Jabodetabek area. This research is a replication of a previous study conducted in the hotel sector, with adjustments made to the tour & travel industry context. This study uses a quantitative approach with descriptive methods. Primary data were collected through questionnaires distributed to 138 tour & travel business owners in the Jabodetabek area. Data analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS version 4.1.1.2. The results show that market orientation does not have a direct significant effect on business performance. However, market orientation has a significant effect on price strategy, and price strategy significantly affects business performance. In addition, price strategy fully mediates the relationship between market orientation and business performance. The conclusion of this study indicates that market understanding needs to be translated into an appropriate pricing strategy in order to have a real impact on improving business performance.